1982
DOI: 10.3758/bf03330276
|View full text |Cite
|
Sign up to set email alerts
|

Sustained visual attention in deaf and hearing adults

Abstract: Benedetti and Loeb (1972) have established that loss of vision (blindness) can be associated with enhancement in the quality of auditory vigilance. The present study demonstrates that loss of hearing (deafness) can result in an analogous enhancement with regard to visual vigilance. Legally deaf and normal-hearing adults monitored a visual display continuously for 45 min. Critical signals for detection were occasional increments in the horizontal movements of a bar of light. The deaf observers detected signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Their CPT used visually presented geometrical shapes as stimuli and the task was to detect a certain type of shape based on whether the object had a hole toward its top or bottom. In contrast to the findings of Dittmar et al (1982), Parasnis et al reported deficits in performance of deaf adults compared with normalhearing participants. It is unclear to what degree the geometric stimuli were verbally encoded (for instance, as "top" or "bottom").…”
mentioning
confidence: 40%
See 1 more Smart Citation
“…Their CPT used visually presented geometrical shapes as stimuli and the task was to detect a certain type of shape based on whether the object had a hole toward its top or bottom. In contrast to the findings of Dittmar et al (1982), Parasnis et al reported deficits in performance of deaf adults compared with normalhearing participants. It is unclear to what degree the geometric stimuli were verbally encoded (for instance, as "top" or "bottom").…”
mentioning
confidence: 40%
“…Dittmar, Berch, and Warm (1982) used a CPT that required 45 minutes of visual monitoring of a light-bar that executed a string of paired movements. The task was to respond when the degree of movement differed between the two paired movements.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, sensory impairment has been found to be a beneficial factor in vigilance performance. Benedetti and Loeb (1972) have reported that blind observers performed more effectively than sighted observers on an auditory vigilance task and Dittmar et al (1982) found superior performance for deaf as compared to normal hearing observers on a visual vigilance task. The utility of these findings for the selection issue is limited, however, by the availability and acceptance of blind and deaf observers for monitoring assignments in operational environments such as military surveillance, airport security, or medicine.…”
Section: Sensory Acuity and Aptitude Measuresmentioning
confidence: 97%
“…attention in a visual vigilance task (Dittmar et al 1982) and visual processing in search tasks (Stivalet et al 1998). These studies suggest that, because deaf adults cannot use audition as an alerting modality, they have developed more proficiency than hearing adults in scanning the visual field for spatially uncertain events.…”
mentioning
confidence: 89%